2020
DOI: 10.3389/fmech.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Life in Single Cell Contact Mechanics: Outstanding Challenges and Perspectives

Abstract: Cell mechanics is a fascinating subject that has witnessed a boost of scientific interest in the most diverse disciplines. Evidence of its biological relevance is continuously mounting, unveiling a real-life scenario ever more intricate and complex, and ever less universal. This review revisits the topic at the same time that appraises routine approaches and the synchronous combination of experimental methodologies to tackle cell mechanics in all its dimensionality and complexity. The focus is placed on cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 127 publications
(129 reference statements)
0
13
0
Order By: Relevance
“…For example, quantifying both cell mechanical properties and signalling events simultaneously might yield a more complete picture of how mechanics, force generation and biochemical signalling are coupled across scales, from single receptor–ligand interactions to cell morphological changes driven by the actin cytoskeleton, to the overall mechanical properties of the tissue environment. Recent efforts of combining AFM with TFM as well as with different fluorescence imaging approaches have already proven to be promising [ 36 , 87 , 90 , 91 , 92 , 93 ]. Quantifying the mechanobiology of the immune response utilizing methodologies with the appropriate sensitivity may thus be the route to enhancing our understanding of the role of mechanobiology in health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, quantifying both cell mechanical properties and signalling events simultaneously might yield a more complete picture of how mechanics, force generation and biochemical signalling are coupled across scales, from single receptor–ligand interactions to cell morphological changes driven by the actin cytoskeleton, to the overall mechanical properties of the tissue environment. Recent efforts of combining AFM with TFM as well as with different fluorescence imaging approaches have already proven to be promising [ 36 , 87 , 90 , 91 , 92 , 93 ]. Quantifying the mechanobiology of the immune response utilizing methodologies with the appropriate sensitivity may thus be the route to enhancing our understanding of the role of mechanobiology in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is essential to differentiate between the macroscopic, or “bulk”, mechanical properties of cells and their microscopic subcellular mechanical properties. Moreover, both the macroscopic and microscopic mechanical properties of cells as well as the forces they generate are time dependent, because their dynamics rely on a constant re-arrangement and molecular turnover [ 10 , 36 , 37 ]. Some processes, for example, actin turnover, occur at the time scale of seconds [ 10 ], while others, such as the re-location of the nucleus of activating T cells, may take multiple hours [ 38 , 39 , 40 ].…”
Section: Mechanics Of Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a biophysical point of departure for investigating the mechanical age-related changes in T cells is that changes in the mechanical properties of cells are hallmarks of ageing (Refs 88 , 89 ). Cell mechanical behaviour has been largely overlooked in the context of the immune system (Refs 90 , 91 ). Outside of the immune system, studies have demonstrated that there is a strong correlation between age and cell stiffness, in numerous diseases, including vascular degeneration, cardiac dysfunction and cancer (Ref.…”
Section: Explaining T-cell Ageing and Relationship With Biophysical F...mentioning
confidence: 99%
“…We and others have spent significant efforts in evolving the sensitivity of traction force microscopy, probably the most widely applied force quantification methodology, which offers the simultaneous quantification of mechanical force production and the dynamics of cells (Colin-York and Fritzsche, 2018 ; Colin-York et al, 2019a ; Stubb et al, 2020 ; Vorselen et al, 2020 ). More recent efforts of combining different types of quantitative simultaneous measurements hold the promise to achieve a more complete understanding of how biomechanics feeds into immune cell physiology of the immune response (Skamrahl et al, 2019 ; Hobson et al, 2020 ; Moreno-Flores, 2020 ; Nelsen et al, 2020 ). Quantifying the mechanical settings of the immune response in full utilizing methodologies with the right sensitivity may thus be the route to enable broad recognition of mechanobiology in health and disease.…”
Section: Future Perspectivementioning
confidence: 99%